(untitled) (Journal “Crop Production, Selection And Seed Production, Fruit And Vegetable Growing”, 2026)
Abstract. This article presents the results of a study aimed at identifying and selecting the optimal rootstock-scion combination for citrus crops for the grafting of сalamondin (Citrus mitis (Blanco)). The objective of the study was to identify the most suitable rootstock for grafting, ensuring the viability, growth and development of plants in container culture. The study was conducted in the acclimatisation chamber of the biotechnology laboratory and in the lecture halls of the Faculty of Agricultural Biotechnology and Food Technology at the Bila Tserkva National Agrarian University. Five species of citrus rootstocks of different growth types and origins were used and evaluated: lemon Citrus limon (L.) Osbesk of the Bel Goy variety, macrophylla Citrus macrophylla (Wester.), mandarin Citrus reticulata (Blanco), lime Citrus aurantifolia (Chrstm.) Swingle and pomelo Citrus maxima (Burm.) Merr. The plants were assessed for their suitability both for pot culture and for use as rootstocks for calamondin Citrus mitis (Blanco). Research has shown that lime and macrophylla rootstocks are the best rootstocks for calamondin (Citrus mitis (Blanco)) in this experiment and ensure good growth and development of the grafted plants. Scions of various citrus species differed in their growth characteristics, with calamondin plants grown on medium-sized rootstocks exhibiting the best development.